Gustave Percival Wiksell papers - Wiksell, Gustave Percival
Correspondence, chiefly between Wiksell and Horace Traubel, relating to personal matters and literary topics especially Walt Whitman. Also includes manuscripts, drafts, and proof sheets of poetry and prose by Traubel; Walt Whitman fellowship agendas and articles; clippings; printed matter; and other papers. Correspondents include Leon Bazalgette, Thomas Bird Mosher, and Anne Montgomerie Traubel.
Dentist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bazalgette, Leon, -- 1873-1928 -- Correspondence; Mosher, Thomas Bird, -- 1852-1923 -- Correspondence; Traubel, Anne Montgomerie, -- 1864-1954 -- Correspondence; Traubel, Horace, -- 1858-1919.; Traubel, Horace, -- 1858-1919 -- Correspondence; Whitman, Walt, -- 1819-1892.; Walt Whitman Fellowship; American literature; American poetry; Literature -- Societies, etc; Dentists